2018
DOI: 10.1101/320903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant trichomes and a single geneGLABRA1contribute to insect community composition on field-grownArabidopsis thaliana

Abstract: 25Background: Genetic variation in plants alters insect abundance and community structure in

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…A single origin of malpighiaceous and stellate trichomes is also not supported by our and others’ data 27 , which could be attributed to the complex genetic control of trichome development 47 . Trichome types have not been studied in the context of family-wide diversification rates and species richness, and thougha selective advantage has been discussed 48 , there may also be fitness costs depending on environmental conditions 49 . In contrast, another trichome character (B03, multicellular glandular hairs) was indeed phylogenetically constrained, both regarding disparity and character occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A single origin of malpighiaceous and stellate trichomes is also not supported by our and others’ data 27 , which could be attributed to the complex genetic control of trichome development 47 . Trichome types have not been studied in the context of family-wide diversification rates and species richness, and thougha selective advantage has been discussed 48 , there may also be fitness costs depending on environmental conditions 49 . In contrast, another trichome character (B03, multicellular glandular hairs) was indeed phylogenetically constrained, both regarding disparity and character occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…All monitoring was conducted by a single observer during the daytime (08:00-17:00) for 3 weeks after the beginning of the field experiment to minimize variation. Details of insect abundance and diversity are reported in our previous publication (Sato et al 2018). In case wounding activated plant defense responses via JA signaling (e.g., Mewis et al 2005; Broekgaarden et al 2010; Matthes et al 2010), we did not sample any leaves until the end of the field experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In wild populations, A. thaliana has multiple life-cycles within a calendar year (Thompson 1994; Wilczek et al 2009; Taylor et al 2017) and is attacked by various herbivores (Arany et al 2008; Harvey et al 2008; Sato et al 2018). Sato et al (2018) observed both flowering and vegetative A. thaliana co-occurring and being wounded by insect herbivores in a wild population near Zurich, Switzerland in summer. By simulating the summer cohort, our previous study found that 12 insect species, including mustard aphids Lipaphis erysimi (Homoptera), flea beetles Phyllotreta striolata and P atra.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations